2010
DOI: 10.1016/j.molcel.2010.05.004
|View full text |Cite
|
Sign up to set email alerts
|

Simple Combinations of Lineage-Determining Transcription Factors Prime cis-Regulatory Elements Required for Macrophage and B Cell Identities

Abstract: Summary Genome-scale studies have revealed extensive, cell type-specific co-localization of transcription factors, but the mechanisms underlying this phenomenon remain poorly understood. Here we demonstrate in macrophages and B cells that collaborative interactions of the common factor PU.1 with small sets of macrophage- or B celllineage-determining transcription factors establish cell-specific binding sites that are associated with the majority of promoter-distal H3K4me1-marked genomic regions. PU.1 binding i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

162
11,073
4
13

Year Published

2013
2013
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10,967 publications
(11,675 citation statements)
references
References 52 publications
162
11,073
4
13
Order By: Relevance
“…Among them are YY1 and E2F3, which show increased motif activity upon JQ1 treatment, and LEF1, FOSL1, and ZNF281, which show decreased motif activity (Figure 6(A)). To further refine TF candidates into BRD2-dependent or independent pathways, we performed motif search analysis by HOMER [33] using BRD2 binding sites of JQ1-upregulated and downregulated promoters. The downregulated promoters were enriched in ZNF281-binding motifs (Figure 6(B), left), while E2F4- and YY1-binding motifs were enriched in the upregulated promoters (Figure 6(B), right).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Among them are YY1 and E2F3, which show increased motif activity upon JQ1 treatment, and LEF1, FOSL1, and ZNF281, which show decreased motif activity (Figure 6(A)). To further refine TF candidates into BRD2-dependent or independent pathways, we performed motif search analysis by HOMER [33] using BRD2 binding sites of JQ1-upregulated and downregulated promoters. The downregulated promoters were enriched in ZNF281-binding motifs (Figure 6(B), left), while E2F4- and YY1-binding motifs were enriched in the upregulated promoters (Figure 6(B), right).…”
Section: Resultsmentioning
confidence: 99%
“…Since LEF1- and FOSL1-binding motifs were not identified in the downregulated genes, they may be involved in the non-BRD2 regulatory pathway. Indeed, our HOMER [33] motif enrichment analysis identified that LEF1- and FOSL1-binding motifs were enriched within H4K5acK8ac peaks without BRD2 binding (Figure 6(C), left). Examples of promoters without BRD2 are shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…H3K27ac data of the samples within the same subgroup were combined. For each subgroup, nucleosome free regions (NFRs) were identified using the “findPeaks” function of HOMER 26 (http://homer.salk.edu/homer/ngs/index.html) with option “-nfr”. ENCODE transcription factor motifs and their mapped positions in the genome were downloaded from http://compbio.mit.edu/encode-motifs/.…”
Section: Methodsmentioning
confidence: 99%
“…We further examined the variable CpGs (with DNA methylation IQR ≥ 5%) in terms of their genomic features (promoter, 5ʹ-UTR, exon, intron, 3ʹ-UTR, TTS, and intergenic) and CpG content (island, shores, shelves, open seas). Genomic features of the CpGs were annotated using Homer annotatePeaks function (hg19) [33]. …”
Section: Methodsmentioning
confidence: 99%